Manajemen Sistem Kinerja Karyawan yang Terintegrasi Efisien dan Transparan di PT Pupuk Iskandar Muda - Nurul Ismi; Suci Mahdianti; Usman Usman; Fachrian Fachrian; Aidil Azhar (Fakultas Teknik, 2023)
AbstractThe management of the Key Performance Indicator (KPI) system by PT Pupuk Iskandar Muda was previously still used to fill out KPI forms and required a process of collecting supporting documents. This impacts the assessment process's duration and the error in inputting values in the scoring system. So, we need an employee performance appraisal system that can improve time efficiency and the accuracy of the assessment. PT PIM innovated an Efficient and Transparent Integrated Employee Performance System Management program, which aims to measure employee performance which is the basis for competency improvement, career planning, and development, calculation of remuneration, awarding achievement incentives and achieving company performance targets. PT Pupuk Iskandar Muda first implemented this innovation in 2021, which began with the preparation of individual KPI contracts, socialization of individual KPIs, and employee training. The implementation of the program at PT PIM has been running since 2022. The environmental impact caused by the generation of waste is reduced by an absolute value of 0.525 tons and cost savings of IDR 10.080.000.Keywords: management, KPI, efficient, transparent, paper waste